Organisational responses to labour shortage problems in Singapore - Tan, Kian Loy (2015)
In Singapore, almost all sectors face labour shortage problems. Many factors have contributed to this problem. These include: a greying population: lower women participation rate: and early retirement at 55 years. Yet other causes include parental pressure for their children to achieve academic qualifications and hence an extended period of schooling which delays entry to the labour market. Also the push for academic qualifications results in preference for managerial jobs thus creating a critical shortage for clerical staff across the economy. Non-competitive renumerations also result in job hopping, further aggravating the problem. To combat these problems, some organisations have adopted the 3R approach, that is recruit. retrain and retain. These organisation also engage in the employment of retirees, part-timers and foreign workers to supplement their existing workforce. In response to the government's recommendation, most unionised companies have raise their retirement age from 55 to 60 years old. Most organisations try to tap the pool of female . workers by providing them certain benefits such as flexible work schedule and childcare center services. Furthermore, many companies are switching to automation to cut down on the use of labour. Due to the improvement m the life expectancy of the general population. the government is planning to come up with a legislation raising the retirement age from 55 to 60 years old after the 3-year grace period for organisations to voluntarily raise the retirement age expires in 1992. Financial assistance in the form of a 50% capital grant by the government is to be given to companies which set up a workplace childcare centre under a proposed scheme. The grant is for the furnishing and equipping of a childcare center. The government is also encouraging organisation to retain their workers by subsidising their training cost through the Skills Development Fund. The government has also relaxed immigration laws to allow more professionals from such areas as Hong Kong and Malaysia to become permanent residents in Singapore.